(untitled) (Heritage, 2022)
In contemporary aspectological researches, especially in those within the domain of the category of the aspect of the verb lexemes formalized as a binary category, there are more and more researches oriented to the empirical verification of claims about its non binary nature. This paper also has such orientation, more precisely in the paper on the example of the verb držati, its reflexive form držati se, and its grammatical derivatives (e.g. udržati, sadrža(va)ti, podržati, pridržavati (se), pridržati (se), prodržati etc.; registered in the consulted dictionaries), we try to show that the category of aspect of the verbs is more complex system than the binary one, i.e. that there are a numerous typological grammatical structures by which the category of verbal aspect, which is inherent in each verb, can be formalized.